(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
Recently, the debate on the need for comprehensive judicial reform in our country has intensified. The nomination of two male candidates (whose specifications were ultimately not accepted by the Senate of the Nation) for the formation of the Supreme Court of Justice of the Nation (CSJN) made the debate more urgent and necessary. Despite this situation, the discussion about judicial reform is not current; at least in legal sociology it has had uninterrupted debates for more than 25 years and it has been the women’s and feminist movements who have promoted it in recent years. In this work, we address the claim of legal feminisms and the proposals made for a feminist judicial reform according to some authors and organizations specialized in the subject. In addition, the axes or aspects whose reform the national State itself recognizes as necessary are also shown. Keeping in mind the possibility of a Court made up entirely of men and that the parity integration of the judicial power is one of the axes on which both legal feminisms and the State itself agree, we develop the main arguments that support parity as a democratizing strategy in the judiciary. We close this contribution with some notes to continue reflecting.